The impact of financial hardship in childhood on depression and anxiety in adult life: Testing the accumulation, critical period and social mobility hypotheses. (August 2020) - Morrissey, Karyn; Kinderman, Peter
Abstract: This paper examines the association between financial hardship in childhood and adulthood, and depression and anxiety in adulthood with reference to the accumulation, critical period and social mobility hypotheses in lifecourse epidemiology. Using the BBC Stress test, linear regression models were used to investigate the associations for the whole population and stratifying by gender and adjusting for age and highest education attainment. The critical period hypothesis was not confirmed. The accumulation hypothesis was confirmed and stratifying by gender women had a higher estimated mean GAD score if they were poor in both childhood and adulthood compared to men. Our findings do not support the social mobility hypothesis. However, stratifying by gender, a clear difference emerged with upward mobility having a favourable impact (lower) on women's mean GAD scores, while upward social mobility in adulthood did not attenuate the impact of financial hardship in childhood or men. The impact of financial hardship in childhood on later mental health outcomes is particularly concerning for future health outcomes as current levels of child poverty increases in the UK. Highlights: The association between financial hardship in childhood and adulthood, and depression and anxiety in adulthood was tested. A lifecourse approach was used. Two episodes of financial hardship had a greater impact on women's Goldberg Anxiety & Depression score compared to men. Upward mobility had a favourable impact on women's mean Goldberg Anxiety & Depression scores, but not for men.